2010
DOI: 10.1252/jcej.43.575
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Microreactor in the Oxidative Dehydrogenation of Propane to Propylene on Calcium Hydroxyapatite and Magnesium ortho-Vanadate Doped and Undoped with Palladium

Abstract: IntroductionPropylene mainly obtained by naphtha cracking is an important raw material for the petrochemical industry. Since the demand of propylene derivatives has recently exceeded that of ethylene, a lack of propylene is a concern for the middle to long term (Suwa, 2004). Therefore, the development of another technology for the production of propylene is desired. The oxidative dehydrogenation of propane on solid catalysts is one of the most attractive reactions for the production of propylene. In our labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In order to address such thermodynamic issues, it has been reported that periodic operation [12][13][14][16][17][18][19][20][21][22][23][24][25] allowing non-equilibrium conditions can overcome the thermodynamic limitations. [12][13][14][16][17][18][19][20] Periodic operation leading to unsteady conditions, which is out of equilibrium, allows to break a target reaction into plural steps (i. e., reaction splitting) [26] with a solo reactor, and thereby the thermodynamic requirement for the target reaction will be split into multiple steps.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address such thermodynamic issues, it has been reported that periodic operation [12][13][14][16][17][18][19][20][21][22][23][24][25] allowing non-equilibrium conditions can overcome the thermodynamic limitations. [12][13][14][16][17][18][19][20] Periodic operation leading to unsteady conditions, which is out of equilibrium, allows to break a target reaction into plural steps (i. e., reaction splitting) [26] with a solo reactor, and thereby the thermodynamic requirement for the target reaction will be split into multiple steps.…”
Section: Introductionmentioning
confidence: 99%